Species Composition, Distribution and Feeding Guilds of Fishes from Sungai Pulai Seagrass Beds, Malaysia - Ajak, Jimmy (2007)
A study was undertaken to investigate the fish species composition and their temporal and spatial distribution and feeding guilds in the Sg. Pulai seagrass bed. Fish specimens for the study were collected from April 2002 to June 2003 using the trammel nets of 640m in total length and 1.6 m height. Fishes were sampled from three subtidal Sg. Pulai seagrass beds namely Tanjung (Tg.) Adang Darat Shoal, Tg. Adang Laut Shoal and Merambong Shoal. A total of 2371 fish specimens were caught from the three sites representing 72 species and 37 different families. Six most dominant fish species comprising of Triacanthus biaculeatus, Arius maculatus, Arius tenuispinis, Plotosus lineatus, Anodontostoma chacunda and Hi/sa kelee were selected for the study on feeding guilds. Analysis on the feeding guild showed two different types of food-based component viz animal and plant origins. Bivalves, gastropods, crustaceans, copepods and polychaete worms were amongst the major gut content of the animal-based diets while seagrass fragment made up the sole plant-based section. The animal-based diets were consistently recorded from T. biaculeatus A. maculatus A. tenuispinis and P. linaetus stomach contents. All the four fish species showed a carnivorous type of feeding habit. The gut contents of A. chacunda and H. kelee were comparatively filled up with seagrass fragments, bivalves, gastropods and copepods, indicating the omnivorous type of feeding mode of the two clupeids species. These results suggested two major modes of feeding guilds that exist amongst the seagrass fishes. Throbab analyzed showed the similar results with the RLG values. In terms of spatial distribution, Tg. Adang Laut Shoal was inhabited by 28 families that consisted of 43 fish species and 11 of them were inclusive of species from the other study sites. Tg. Adang Darat Shoal was inhabited by 23 families and 37 different species of fishes. Four species found here exclusive to this seagrass bed and not recorded from the other two study sites. The fish caught within Merambong shoal seagrass bed were almost similar in species to the Tg. Adang Laut and Tg. Adang Darat shoals with the exception of Dasyatis zugei and Gerres filamentous. A total of 21 families and 28 species of seagrass fishes were finally recorded in the Merambong Shoal. The study also revealed that several fish species were exclusively confirmed to one particular habitat either the vegetated or the non-vegetated sites. The results also indicated that families Leiognathidae and Engraulidae were consistently been recorded around the seagrass areas throughout the study period. In addition, the results may also indicates that other fish families were not permanent dwellers of the Sg. Pulai seagrass beds and their presence in the study areas could well be due to occasional feeding and spawning activities.